1997
DOI: 10.1172/jci119794
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular adhesion molecule-1 and CD36 synergize to mediate adherence of Plasmodium falciparum-infected erythrocytes to cultured human microvascular endothelial cells.

Abstract: We have compared the adhesion of Plasmodium falciparum -infected erythrocytes to human dermal microvascular endothelial cells (HDMEC) and human umbilical vein endothelial cells (HUVEC) and have assessed the relative roles of the receptors CD36 and intercellular adhesion molecule-1 (ICAM-1). HUVEC (a cell line that expresses high levels of ICAM-1 but no CD36) mediate low levels of adhesion, whereas HDMEC (which constitutively express CD36) mediate high levels of adhesion even before ICAM-1 induction. ICAM-1 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(118 citation statements)
references
References 44 publications
6
110
0
2
Order By: Relevance
“…Fibronectin, through its known interactions with integrin receptors present on endothelium (Albelda et al, 1989), is an ideal candidate molecule to orchestrate these events. Many other invasive pathogens use integrins as cellular receptors (for review see Berendt & McCormick, 1997) and Streptococcus pyogenes has already been shown to invade a number of epithelial cell lines through the interaction between fibronectin and epithelial-cell-surface integrins (Ozeri et al, 1998). Our observations thus prompt the speculation that S. aureus invades endothelial cells through similar mechanisms.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Fibronectin, through its known interactions with integrin receptors present on endothelium (Albelda et al, 1989), is an ideal candidate molecule to orchestrate these events. Many other invasive pathogens use integrins as cellular receptors (for review see Berendt & McCormick, 1997) and Streptococcus pyogenes has already been shown to invade a number of epithelial cell lines through the interaction between fibronectin and epithelial-cell-surface integrins (Ozeri et al, 1998). Our observations thus prompt the speculation that S. aureus invades endothelial cells through similar mechanisms.…”
Section: Discussionmentioning
confidence: 55%
“…The relevant activation status of the endothelial cells in vivo is unknown and their phenotype will vary according to site. We previously showed that there are important differences between microvascular and large vessel endothelium in the expression and function of host receptors for the adhesion of malaria-infected erythrocytes (McCormick et al, 1997). Furthermore, for adhesion of both leukocytes and malaria-infected erythrocytes, endothelial receptors show differential adhesion under shear flow conditions, with ' rolling ' and ' static ' receptors.…”
Section: Discussionmentioning
confidence: 99%
“…A4tres-infected erythrocytes bind both ICAM-1 and CD36. These two proteins have been shown to synergize in mediating infected erythrocyte adhesion to cell lines that express both of these molecules (31). A CD36 binding domain has previously been shown to reside in the CIDR domain of PfEMP1 that bind CD36 (20,21).…”
Section: The Dbl␤ Domain From the A4var Pfemp1 Is Implicated In Parasitementioning
confidence: 99%
“…The activities of some TSP1 receptors differ between large vessel and microvascular endothelial cells, and some are regulated by specific contextual signals (4 -6). CD36, a member of the scavenger receptor B family, is a TSP1 receptor that is selectively expressed in microvascular endothelium (7,8). CD36 was initially reported to recognize CSVTCG sequences in the type 1 repeats of TSP1 (9), but further studies identified higher affinity binding to the adjacent GVQXR sequences in the second and third type 1 repeats (10, 11).…”
Section: Pathological Angiogenesis or The Lack Thereof Underlies A Numentioning
confidence: 99%